New applications for Gelidium corneum: Antimicrobial and antioxidant activity within a biorefinery concept - Mouga, Teresa (2021)
There are more than four hundred endogenous seaweeds that occur in Portugal, and red seaweeds (Rhodophyta) are the most abundant. Among these, Gelidium corneum, common in the Atlantic coast of Portugal, is currently being collected in the wild, in S. Martinho do Porto, exclusively for the extraction of agar. During the summer season this species is harvested from the bottom of the ocean, dried and sold, representing an important economic local activity. Yet, besides agar, this species is important for its bioactivities, namely for its antioxidant and antimicrobial capacities, thus most of the biomass is currently being disregarded as an important marine resource. Therefore, to further research the potential of G. corneum as a source of bioactive compounds, the biomass was seasonally harvested and characterized (protein, ash, moisture), and different extract were made (aqueous and ethanolic). These extracts were analyzed for the antioxidant potential (DDPH, ABTS, TPC and FRAP), and for antimicrobial capacity (against Escherichia coli, Bacillus subtilis, Candida albicans, Saccharomyces cerevisiae and Staphylococcus epidermidis). Preliminary results show that there are seasonal variations in the chemical composition of the biomass. Extracts tested also show interesting free radical scavenging capacity and antimicrobial activity against some of the strains tested. The attained results demonstrate that the biorefinery concept should be implemented to the agar industry, valuing the seaweeds’ biomass so to allow its use in other industries, such as textiles or cosmetics.